Deep sedation vs. general anesthesia for transcatheter tricuspid valve repair - Haurand, Jean Marc; Kavsur, Refik; Ochs, Laurin; Tanaka, Tetsu; Iliadis, Christos; Sugiura, Atsushi; Kelm, Malte; Nickenig, Georg; Baldus, Stephan; Westenfeld, Ralf; Becher, Marc Ulrich; Pfister, Roman; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Transcatheter tricuspid valve repair (TTVr) is routinely performed under general anesthesia (GA). This study aimed to investigate whether TTVr procedures can be performed effectively and safely without GA but using deep sedation (DS). Methods We performed a retrospective analysis of 104 patients from three centers who underwent TTVr between 2020 and 2021. The primary performance endpoints were technical success and severity of TR assessed at the time of discharge. The safety outcome was a composite of in-hospital complications, including occurrence of death, conversion to surgery, major adverse cardiac and cerebrovascular events, major vascular complications, or occurrence of pneumonia. Results Sixty-four procedures were performed in GA and 40 procedures were performed in DS. The groups did not differ in age, EuroScore II, TR severity, ventricular function, or hemodynamic parameters. Technical success was achieved in 92.5% of the patients in the DS group and in 93.6% of the patients in the GA group (p = 0.805). In none of the patients intraprocedural conversion from DS to GA was required. There was no difference in total duration of the procedure, and number of devices implanted. The degree of TR was ≤2+ in 77.5% of the patients in the DS group and in 74.2% of the patients in the GA group (p = 0.705). The composite safety endpoint did not differ between the groups (2.5 vs. 6.3%, p = 0.384). The total duration of hospital stay was shorter in patients who underwent TTVr in DS compared to those who underwent TTVr in GA (6 [5, 9] days vs. 8 [6, 11] days; p = 0.011). Conclusion Performing TTVr in DS was effective with similar procedural results, and was safe with similar low complication rates compared to GA.